Factors Affecting The Purchase Of Vegetables At The Online Store "Kupesan" - Tiarma Tiarma; Yossie Yumiati; Ana Nurmalia (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Advances in science and technology in agriculture have brought changes in buying and selling transactions of fresh agricultural products such as vegetables. This change encourages the lifestyle of people who want everything practical and the emergence of online stores, Kupesan is the first online store in Bengkulu City that already has an application. Therefore, the purpose of this study was to determine the factors that influence purchasing decisions for vegetables at the online shop "Kupesan". Data collection methods were carried out by surveys, interviews and distributing questionnaires via google form. A sample of 67 people using purposive sampling, namely individuals who may be respondents are people who have purchased vegetable commodities more than once at the online shop "Kupesan". Data analysis using multiple linear regression with the help of SPSS software. The results of this study indicate that the factors of trust and product quality that influence purchasing decisions for vegetables at the online store Kupesan. While the factors of price, convenience and service do not affect the decision to purchase vegetables at the online store Kupesan.